KARAKTERISASI KATALIS BATU PADAS LEDGESTONE TERAKTIVASI ASAM DAN APLIKASINYA PADA PEMBUATAN BIODIESEL DARI MINYAK JELANTAH - Juliana, Ika; Widihati, Ida Ayu Gede; Ratnayani, Oka (Jurnal Kimia (Journal of Chemistry), 2016)
This research aims to improve characteristics of ledgestone catalyst by using acid activation with various concentrations. The acid used for activation was H 2 SO 4 with concentrations of 1, 2 and 3M. The characterization of catalysts was carried out by acid-base titration method to determine the surface acidity, methylene blue adsorption to measure the spesific surface area of ??the catalyst, and the NH 4 OAc extraction method to measure the value of cation exchange capacity of the catalyst. Ledgestone catalyst with the best character was applied to convert waste cooking oil into biodiesel. The characterization of biodiesel was carried out by densitometry to determine the density of biodiesel, Oswald viskosimetry to measure the viscosity, and Gas Chromatography-Mass Spectrometry (GCMS) to determine the composition of chemical compounds of the biodiesel. The results showed that the concentration of acid used to activate ledgestone catalyst with the best character was 1M. This acid-activated ledgestone (catalyst A 1 ) had a value of surface acidity, surface area, active sites number, and high cation exchange capacity were 0.3530 ± 0.0011 mmol / gram and35.7581 m 2 /gram, 2.1258 x 10 20 atoms/gram, and 5.88 me/100 g, respectively. The concentration of catalyst A 1 producing the highest biodiesel yield was 1% w/v. The produced biodiesel was 74,71% with 0.02% FFA, acid value of 0.0438 mg KOH/gram biodiesel, density of 0.7850 g/mL, kinematic viscosity of 0.4650 cSt. Two major compounds of the biodiesel were methyl hexadecanoate with area of 71.84% and cis methyl-9-octadecenoate with area of 28.16%.
Keywords: heterogenous catalysts, ledgestone, acid-activated (H2SO4), biodiesel, waste cooking oil